Standardised protocol for a prospective cross-sectional multicentre clinical utility evaluation of two dual point-of-care tests in non-clinical settings for the screening of HIV and syphilis in men who have sex with men - James Kiarie; Karel Blondeel; Igor Toskin; Jordi Casabona; Soe Soe Thwin; Massimo Mirandola; Rosanna Peeling; Ronald Ballard; Laura Fernàndez-López; Inga Upmace; Juliana Reyes-Urueña; Mara Vaselova; et al. (BMJ Open)
Introduction Point-of-care dual tests (POCTs) for simultaneously detecting antibodies to HIV and syphilis (dual HIV-syphilis POCTs) have been developed recently and show encouraging performance compared with the reference tests in laboratory-based studies. As community-based voluntary, counselling and testing (CBVCT) services are effective providers of HIV and syphilis testing and counselling with high acceptability among men who have sex with men (MSM), the evaluation of the utility of these dual tests in CBVCT services is a high priority. This prospective cross-sectional study will conduct a clinical utility evaluation of two dual POCTs in non-clinical settings for the screening of HIV and syphilis in MSM. This master protocol outlines the overall research approach that will be used in four countries.Methods and analysis MSM presenting at CBVCT services participating in the study for HIV/STI screening will be enrolled. The (WHO preapproved) dual POCTs to be evaluated will be SD Bioline HIV/Syphilis Duo (Abbot) and Dual Path Platform HIV-Syphilis Assay (Chembio). Trained staff will collect a capillary blood sample using finger prick blood to perform both POCTs according the manufacturers’ instructions. An analysis of the feasibility of introducing the dual POCT for the screening of HIV and syphilis in MSM at CBVCT services will be performed, by assessing its acceptability and usability at CBVCT service among MSM users and providers.Ethics and dissemination This core protocol was independently peer reviewed and approved by the Research Project Review Panel (RP2) of the WHO Department of Sexual and Reproductive Health and Research and by the WHO Ethics Review Committee (ERC). The protocol has been adapted to individual countries and approved by RP2, ERC and institutional review boards at each site. Results will be disseminated through peer-reviewed journals and relevant conferences.